PEMANFAATAN ANALISIS REGRESI DAN AMMI UNTUK EVALUASI STABILITAS HASIL GENOTIPE PADI DAN PENGARUH INTERAKSI GENETIK DAN LINGKUNGAN - Widyastuti, Yuni (Informatika Pertanian, 2013)
Some statistical analyses were employed to depict responses of genotype (G) on environment (E). Regression analysisreflects the average index of G x E to calculate the genotype responses to heterogenous environment. Regression deviationwas employed to count the stability of the result obtained through such a method, which, further be developed to testthe average effect of G x E through a combination of additive effects of multivariate analysis with multiplication effecton the primary component (AMMI model). Regression analysis showed that Ciherang, Hibrindo R1, IH806 hybrid wasmore superior than others in terms of stability andproduct adaptability, whereas IH805, IH808, and IH809, are specificfor locations Batang, Jember, Ngawi, and Madiun, respectively.